The Effect of Six Sigma on Quality, Innovation Capability and Work Productivity of Tyre Industries - Fahmi, Khaerul; Mustofa, Ali; Rochmad, Imbuh; Sulastri, Eva; Wahyuni, Indah Sri; Irwansyah, Irwansyah (Journal of Industrial Engineering & Management Research, 2019)
- This research is an empirical study on the Tire Industries in Jakarta, Indonesia. The main objective of this research is to analyze the practical and strategic effects of the implementation of Six Sigma on innovation capabilities, work productivity, and quality to customers as part of the comparative and competitive advantages of companies engaged in tire industries. The population of this research is all employees of tyres industries. Sampling using a questionnaire with a simple random sample technique that is distributed to the entire population. The number of incoming and valid questionnaires was 443 samples. Data processing using the SEM method with SmartPLS 3.0 software. From the results of data analysis, it can be seen that all hypotheses are accepted, indicating that the implementation of the Six Sigma has a positive and significant effect on innovation capabilities, work productivity, and quality. Innovation capabilities and employee work productivity also have a positive and significant effect on quality. Another important point is that innovation capability and work productivity have a positive and significant effect as a mediator on the influence relationship between the Six sigma and service quality. This study proposes a model to improve the quality of tyre industries through increasing and strengthening the application of the Six Sigma concept through innovation capabilities and work productivity as a mediator. This research can pave the way for increasing the readiness of employees and companies to face the era of the industrial revolution 4.0.